2007
DOI: 10.1016/j.chom.2007.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Host-Mediated Inflammation Disrupts the Intestinal Microbiota and Promotes the Overgrowth of Enterobacteriaceae

Abstract: While the normal microbiota has been implicated as a critical defense against invading pathogens, the impact of enteropathogenic infection and host inflammation on intestinal microbial communities has not been elucidated. Using mouse models of Citrobacter rodentium, which closely mimics human diarrheal pathogens inducing host intestinal inflammation, and Campylobacter jejuni infection, as well as chemically and genetically induced models of intestinal inflammation, we demonstrate that host-mediated inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
685
7
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,032 publications
(761 citation statements)
references
References 48 publications
47
685
7
3
Order By: Relevance
“…Antibiotics can have longlasting effects on the microbiota; deep sequencing of the microbiome from three adults before and after ciprofloxacin treatment has shown that most taxa recover by 4 weeks, but some taxa take much longer to recover (13) . Similar results have been obtained in mice (14) , in which it has also been shown that an intestinal pathogen (in this case Citrobacter rodentium) perturbs the microbiota but the pretreatment status quo returns within 28 d (15) . Importantly, the microbiome tends to recover a composition characteristic of that individual even after treatment with a broad spectrum antibiotic, despite the apparent opportunity that this treatment represents for a change in the flora and that is sometimes exploited by Clostridium difficile (16) .…”
Section: What Is the Microbiome?supporting
confidence: 81%
“…Antibiotics can have longlasting effects on the microbiota; deep sequencing of the microbiome from three adults before and after ciprofloxacin treatment has shown that most taxa recover by 4 weeks, but some taxa take much longer to recover (13) . Similar results have been obtained in mice (14) , in which it has also been shown that an intestinal pathogen (in this case Citrobacter rodentium) perturbs the microbiota but the pretreatment status quo returns within 28 d (15) . Importantly, the microbiome tends to recover a composition characteristic of that individual even after treatment with a broad spectrum antibiotic, despite the apparent opportunity that this treatment represents for a change in the flora and that is sometimes exploited by Clostridium difficile (16) .…”
Section: What Is the Microbiome?supporting
confidence: 81%
“…Selective species of E. faecalis have been shown to antagonize diarrhea induced by E. coli K88 through unknown mechanisms (32), but it is conceivable that not all strains of E. faecalis will have beneficial effects. Moreover, it was recently shown that the intestinal ecosystem is altered in cases of inflammatory reaction to stimuli in the host (33). Importantly, the composition of the microbiota is restored after dissipation of the inflammatory signal, a feature of a healthy homeostatic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…or pathogenic E. coli strains can suppress the anaerobic microbiota and boost enterobacterial colonization densities (20)(21)(22)(23)(24). Here, we show that disease-triggered enterobacterial blooms can fuel HGT between two prominent members of this family, Salmonella enterica serovar Typhimurium (S. Tm) and E. coli.…”
mentioning
confidence: 94%